O ensino de gramática na Paraíba em Lições da Língua Materna (1906) - Ramos, Maria Daniela Angelo (2014)
This research aims to analyze the teaching of grammar in the book Lições de Língua Materna Lessons from the Mother Tongue (1906) by Francisco Xavier Junior, adopted by a decree law n. 315 - January 17, 1907 - of the State Government as the only book to be used in Paraíba primary schools for the Teaching of Portuguese Language. Therefore, we took in consideration that in this period marked by nationalist ideals there was a proliferation of educational books with knowledge that would satisfy the progress and nationalism. This way, to produce books that valued the teaching of the mother tongue was a mean to reinforce the idea that every language has a grammar, which serves to unify the member of a society through a set of values, rules and ideals. We got as theoretical reference for development of this research Bittencourt (2004), Razzini (2000), Fávero (2009), Galvão and Batista (2003), Lajolo and Zilberman (1996)- Educational books. About outhorship, production work process and the reading protocols we used Chartier (1999), as well Foucault (2012) to analyze the speeches present in the work. After we realized the speeches analysis and the contents we have seen that the book "Lições da Língua Materna" followed this tendency to innovate teaching methods of Portuguese grammar based on the intuitive method, answering the republican modernization project. The book contains practical, rational exercises and explains grammatical content in an objetive manner, emphasizing the practice instead of valorizing the exhaustive memorization of rules, as in traditional teaching. Furthermore, it was verified that when the book teaches standardized knowledge, it also contributes with the tasks of homogenize/unify through a common referential, the mother tongue.